A STUDY OF WASTEWATER MANAGEMENT AT COT SEUMEUREUNG AND PEUREUMEU COMMUNITY HEALTH CENTERS WEST ACEH REGENCY - Siti Yasrah; Lili Eky Nursia N.; Ihsan Murdani; Wintah Wintah; Fikri Faidul Jihad (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
As healthcare facilities, community health centers (puskesmas) generate wastewater that contains pathogenic microorganisms, hazardous chemicals, and toxic substances, which have the potential to pollute the environment and pose risks to public health if not managed according to standards. Although the Ministry of Health Regulation No. 7 of 2019 mandates that every puskesmas should have a functioning Wastewater Treatment Plant (IPAL), many puskesmas in West Aceh District, including Puskesmas Cot Seumeureung and Peureumeu, have not yet operated their IPAL optimally. This study aims to assess the wastewater management at these two puskesmas and the role of the West Aceh Health Office in supervision and guidance. The research employs a descriptive qualitative approach, using data collection techniques such as interviews, observations, and documentation from seven informants at both puskesmas and the Health Office. The data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that at Puskesmas Cot Seumeureung, only some rooms are connected to the IPAL due to limited pipeline infrastructure, while at Puskesmas Peureumeu, pipe leaks that have remained unrepaired for two years were found. Additionally, the monitoring of water quality and maintenance of the IPAL at both puskesmas are still minimal, with pH test results frequently exceeding the standard limits. The management of wastewater at these puskesmas remains suboptimal, requiring improvements in infrastructure, regular monitoring, and capacity-building for human resources.